MICROBIAL FUEL CELL (MFC) BY ELECTROACTIVE BACTERIA AS A RENEWABLE ELECTRICAL ENERGY SOURCE IN INDONESIA - Nazla Fauziyah Octaviani; Nisa Kartika; Anggita Rahmi Hafsari (Indonesian Journal of Environmental Sustainability, 2023)
The uncontrolled nature of fossil fuels and their ecological consequences have moved emphasis to renewable energy and fuel cells, particularly in the transportation industry. The generation of energy from electrons generated from metabolic reactions aided by bacteria is studied in this paper. Microbial fuel cells (MFC) are an environmentally beneficial method of generating electricity while also purifying wastewater, with up to 50% chemical oxygen requirement elimination and power densities ranging from 420 to 460 MW/m2. This paper focuses on the technology that generates electricity by utilizing the metabolic power from electroactive bacteria as a renewable energy source. The method to collect data is a literature study. The result is seven species of electroactive bacteria potential from 7 articles, which can be used to generate MFC. In summary, using electroactive bacteria as MFC as a renewable energy source is possible because many sources of organic materials can be used as carbon sources for MFC, such as organic waste.